THE INFLUENCE OF PROMOTIONAL COSTS ON SALES OF BEAT ESP MOTORS ON THE DEALER OF TDM MOTORCYCLES FOR PUTRI GREEN, NORTH BENGKULU - Wahid Nugroho; Ahmad Soleh; Kaulan (Penerbit Jurnal Indonesia, 2020)
The main purpose of the company in conducting marketing activities is to increase sales results or at least maintain the existing market.This study aims to determine the effect of promotional costs on sales volume at TDM Motor PutriHijau Bengkulu Utara. Based on the results of promotion costs have a positive effect on sales at the TDM Motor Dealers PutriHijau Bengkulu Utara, which is shown by the linier regression equation Y = 85,785,605+ 0.58X, meaning that the ups and downs of promotion costs on the TDM Motor Dialer effect the ups and downs of sales by 0,58, and if the promotion costs are constant, the Beat ESP motorbike at the TDM Motor Dealer is 85,785,605. There is a moderate relathionship between promotion costs and sales of TDM Motor PutriHijau Bengkulu Utara Dealers shown by the value r = 0,56 with the criteria of medium value, because the value of r = 0,56 lies in the interval coefficient of 0,400 – 0,599, determination test vaslue of Kd = 30% meaning that the influence of promotion costs on sales is 30%, while the remaning 69% is influenced by other factors an is a factor not examined in this study. The results of testing the hypothesis are known tcount> t tabel (3.1620>1.71714), then H0 is rejected and accepts H1 or the correlation is significant, meaning that there is a positive and moderate effect between the cost of promotion towards the sale of Beat ESP motorcycles at TDM Motorbike Dealers of PutriHijauBengkuylu Utara.